Agritourism as a catalyst for sustainable rural development: Exploring its multifunctional prospects (vol 20, 0068, 2025) - Sharma, Saurabh; Maisnam, Guneshori; Thangjam, Deepa; Choudhary, Ravish; Kirbag, Sevda; Sushkova, Svetlana; Assouguem, Amine (Cabi Publishing, 2025)
[Abstract Not Available]